2015
DOI: 10.1890/es15-00112.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the factors affecting leaf litter decomposition across a tropical forest disturbance gradient

Abstract: Deforestation and forest degradation are driving unprecedented declines in biodiversity across the tropics, and understanding the consequences of these changes for ecosystem functioning is essential for human well‐being. Forest degradation and loss alter ecosystem functioning through changes in species composition and abiotic conditions. However, the consequences of these changes for heterospecific processes are often poorly understood. Leaf litter decomposition is a major source of atmospheric carbon and crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 57 publications
(72 reference statements)
3
49
0
4
Order By: Relevance
“…Twenty‐eight 100 × 100 m plots were set up from April 2010 to May 2011, based on a stratified random sampling design described in Paudel et al . (,b) (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐eight 100 × 100 m plots were set up from April 2010 to May 2011, based on a stratified random sampling design described in Paudel et al . (,b) (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, seasonal snow cover is particularly critical in arid regions and can greatly affect regional ecological processes (Paudel et al. , He et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition rates have been shown by several previous studies to be greatly reduced when tropical forests are converted to anthropogenic pasture or agricultural use (Lorenzo et al., ; Paudel et al., ; Szefer et al., ). Our study similarly revealed reduced decomposition rates in anthropogenic pasture compared to forest.…”
Section: Discussionmentioning
confidence: 96%
“…(); (4) Paudel et al. (); (5) Barlow, Gardner, Ferreira & Peres, (); (6) Xuluc‐Tolosa, Vester, Ramırez‐Marcial, Castellanos‐Albores & Lawrence (); (7) Ewel (); (8) Mendoza, Gallardo, Turrion, Pando & Acenolaza (); (9) Ostertag, Marin‐Spiotta, Silver & Schulten (); (10) Vasconcelos & Laurance (); (11) Barajas‐Guzmán & Alvarez‐Sánchez (); (12) Gove et al. (); (13) Cole, Holl, Zahawi, Wickey & Townsend (); (14) Piper, Catterall, Kanowski & Proctor (); (15) Grimbacher et al., (); (16) Nakamura et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation